A concise study on the floral biology of Thevetia peruviana morphovariants - Nesy, E. A.; Mathew, Lizzy (Current Botany, 2023)
Thevetia peruviana, an ornamental medicinal plant of the family Apocynaceae blooms in different colour shades of yellow, orange and white, and is considered morphological replicas of its original parental type. A concise morpho-anatomical study has been carried out on the floral biology of these three morphovariants emphasizing biometrics of various floral parts, the architecture of corolla tube and corolline corona, adnation of anther stigmatic head complex and ovule to embryo formation, using the hand as well as microtome sections, to analyze the similarities and differences among these specimens. Appendiculate and smooth walled hairs in corolla tube, germination of pollen grains in a lateral stigmatic notch, appression of anther lobes on 10-lobed incompletely fused stigma, triaperturate pollen grains, ovule developmental stages, entry of pollen tube into ovule, attachment of funicle on placenta etc are some of the enchanting valuable scientific observations under light microscopy. Gross morphological variations noted in the overall size of various floral parts are regarded as negligible ones, which may happen due to environmental factors. Floral morphology alone is insufficient to give distinct varietal status in the hierarchy of classification, but corolla shades, of course, are of prime importance for phenotypic differentiation, and a multidisciplinary approach will help to expose untapped characters, useful for future studies below the rank at the subspecies level.